EFEKTIVITAS BADAN USAHA MILIK DESA (BUM Desa) DALAM PENGELOLAAN POTENSI DESA TANJUNG PUNAK KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS - Roni Fasla; Adianto; Hasim As’ari (Journal Publicuho, 2022)
This paper discusses the effectiveness of the management of BUM Desa Punak Mandiri in managing the potential of Tanjung Punak Village, North Rupat District, Bengkalis Regency. Tanjung Punak Village has potential in the tourism sector, especially marine tourism. BUM Desa Punak Mandiri is expected to be able to develop this potential. In addition, it is also expected to be able to empower the community through business incubation. This study uses a descriptive qualitative method. The author collected secondary data (journals, finance related to BUM Desa, and statistical data) and primary data (in-depth interviews and observations). This research is located at BUM Desa Punak Mandiri, which is located at Tanjung Punak Village, North Rupat District. The results of this study are first, there are internal constraints in the effectiveness of developing village potential and community business incubation. Second, there are constraints due to the Covid-19 pandemic, some business units cannot operate, which affects the business turnover of the BUM Desa.